FISH FOR LIVELIHOODS (F4L) MIDLINE STUDY DATASET IN MYANMAR - Brako Dompreh, Eric; Khaing, Htet (2024)
A comprehensive dataset was collected in 2024 from 800 households across 6 diverse regions of Myanmar to discover the impact of adopting Better Management Practices (BMPs) on local livelihoods. Data collection focused on assessing socio-economic characteristics, production characteristics, household-level knowledge, attitudes, and practices concerning improved aquaculture techniques.